Impact of alternative wood ageing systems in the odorant profile of wine spirits with GC-O analysis - Zarpellon, Damiano (2019)
Mestrado em Engenharia de Viticultura e Enologia (Double Degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto